ALK Inhibitors, a Pharmaceutical Perspective - Galvani, Arturo; Ardini, Elena (Frontiers in Oncology, 2012)
In 2007, the ALK tyrosine kinase, already known to be translocated and activated in Anaplastic Large Cell Lymphoma, and a few other rare cancers, was described as a potential therapeutic target for a subset of non small-cell lung cancer (NSCLC) patients. Clinical proof of concept, culminating in the recent approval by the FDA of the Pfizer drug Xalkori (crizotinib, formerly known as PF-02341066) followed in record time. The drug was approved together with a companion diagnostic, the Vysis ALK Break Apart FISH Probe Kit (Abbott Molecular, Inc.) for detection of eligible patients. This remarkable example of the coming of age of personalized medicine in cancer therapy is hopefully only an auspice of things to come in this rapidly developing field. Perhaps unsurprisingly, however, the appearance of clinical acquired resistance to crizotinib has already been observed early on in clinical testing, with the identification of several ALK secondary point mutations which diminish drug efficacy, and which open the way for development of second-generation inhibitors. It is also emerging that acquired resistance to crizotinib may also occur through ALK-independent mechanisms, which still need to be elucidated in detail.